Association of Salivary Statherin, Calcium, and Proline-Rich Proteins on Oral Hygiene: A Cross-Sectional Study - Deepak Gowda Sadashivappa Pateel; Shilpa Gunjal; Liew Fong Fong; Nur Sulwana Mohd Hanapi (Hindawi Limited, 2021)
Background. Saliva, as a complex biofluid, plays a pivotal role in maintaining oral health and tooth integrity. There has been inconsistent data available on the relationship between salivary parameters and oral health. This study aims to investigate the association between salivary statherin, acidic proline-rich proteins (aPRP), and calcium with oral hygiene status. Methods. One hundred and eighty-eight healthy subjects aged between 18 and 50 years with varying oral hygiene status who gave consent to participate were included in this cross-sectional study. The subjects were recruited from primary oral health care of MAHSA University. Oral hygiene of all the participants was measured using Oral Hygiene Index-Simplified (OHI-S). Stimulated saliva collected using paraffin wax was analyzed for salivary statherin, aPRP, and calcium. The relationship between salivary statherin, aPRP, and calcium levels with OHI-S was assessed using Spearman's Rank correlation coefficient; the strength of relationship was assessed by multiple linear regression analysis. Results. The study found a weak positive correlation (r = 0.179, p = 0.014) between salivary statherin and OHI-S; weak negative correlation (r = −0.187, p = 0.010) between salivary aPRP and OHI-S; and moderate negative correlation between salivary statherin and salivary aPRP levels (r = −0.50, p < 0.001) which were statistically significant. Conclusion. Poor oral hygiene is associated with increased statherin and reduced aPRP levels in saliva. Thus, these salivary components may have a role in predicting oral hygiene status.